ATP hydrolysis provides functions that promote rejection of pairings between different copies of long repeated sequences. Issue 14 (7th July 2017) - Danilowicz, Claudia; Hermans, Laura; Coljee, Vincent; Prévost, Chantal; Prentiss, Mara
Abstract: During DNA recombination and repair, RecA family proteins must promote rapid joining of homologous DNA. Repeated sequences with >100 base pair lengths occupy more than 1% of bacterial genomes; however, commitment to strand exchange was believed to occur after testing ∼20–30 bp. If that were true, pairings between different copies of long repeated sequences would usually become irreversible. Our experiments reveal that in the presence of ATP hydrolysis even 75 bp sequence-matched strand exchange products remain quite reversible. Experiments also indicate that when ATP hydrolysis is present, flanking heterologous dsDNA regions increase the reversibility of sequence matched strand exchange products with lengths up to ∼75 bp. Results of molecular dynamics simulations provide insight into how ATP hydrolysis destabilizes strand exchange products. These results inspired a model that shows how pairings between long repeated sequences could be efficiently rejected even though most homologous pairings form irreversible products.